Evaluation of the Long-Term Impact on Quality After the End of Pharmacist-Driven Warfarin Therapy Management in Patients With Poor Quality of Anticoagulation Therapy - Marcatto, Leiliane Rodrigues; Sacilotto, Luciana; Tavares, Letícia Camargo; Souza, Debora Stephanie Pereira; Olivetti, Natália; Strunz, Celia Maria Cassaro; Darrieux, Francisco Carlos Costa; Scanavacca, Maurício Ibrahim; Krieger, Jose Eduardo; Pereira, Alexandre Costa; Santos, Paulo Caleb Junior Lima (Frontiers in Pharmacology, 2020)
Background Warfarin is the most common oral anticoagulant drug, especially in low-income and emerging countries, because of the high cost of direct oral anticoagulant (DOACs), or when warfarin is the only proven therapy (mechanical prosthetic valve and kidney dysfunction). The quality of warfarin therapy is directly associated with dose management. Evidence shows that pharmaceutical care achieves a better quality of therapy with warfarin. However, there are no studies showing this intervention in a specific patient group with poor quality of anticoagulation in a long period after the end of the follow-up by a pharmacist. Thus, the aim of this study was to evaluate whether the quality of warfarin therapy driven by a pharmacist remains stable in the long term after the end of follow up with a pharmacist, in AF patients with poor quality of anticoagulation. Methods This is a prospective study, which evaluated about 2,620 patients and selected 262 patients with AF and poor quality of anticoagulation therapy with warfarin (TTR<50% - based on the last three values of international normalized ratio). Pharmacist-driven therapy management was performed up to 12 weeks. Data from patients were evaluated 1 year after the end of the follow-up with pharmacist. Results Comparison between mean TTR after 12 weeks of pharmaceutical care (54.1%) and mean TTR one year after the end of the pharmaceutical care (56.5%; p=0.081) did not achieve statistical difference, demonstrating that the increment of quality due to intervention of 12 weeks was maintained for 1 year after intervention. Conclusion The long-term impact of pharmaceutical care was beneficial for patients with AF and poor quality of warfarin anticoagulation. This design might be an important strategy to treat a subgroup of patients without proven effectiveness of warfarin.